If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying a + -4a + -3a = 0 Combine like terms: a + -4a = -3a -3a + -3a = 0 Combine like terms: -3a + -3a = -6a -6a = 0 Solving -6a = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Divide each side by '-6'. a = 0 Simplifying a = 0
| -x+4=-y | | 2x+15x^2=24 | | 7.6-0.7h+1.2-1.3h=24-2.0h-6.7 | | 6.9x-3.6=24.0 | | 6y^2=-7-2 | | 8/3x-21/2 | | 2x+15x^2=32 | | 5x5/5/7 | | 128=8-4e | | 45x+27= | | 2x+15x^2=35 | | x^3+5x^2-4x-2=0 | | 25=-5y-6x | | -6w^2+150w=0 | | 5(2x-17)=10x-85 | | 5x+x^2=y | | -13+3x+4+-5x=15 | | 0.06x-0.10(x-2)=0.02(8) | | 36+7-25+7= | | 4x-15/3=7 | | -2(7x-4)+3(5x-4)-3=7-3 | | 28+p=39 | | 10g+10=29g | | 17.40=1.5n | | 3y=8-2x | | 3x+4(x-8)= | | -7r+14=-71 | | -4(3x+6y)+12x+4y= | | 12x+.50y=112 | | 3cotx+3=8 | | 0=-15-3y+2x | | 25=x+2x+3x+1 |